Manufacturing method of electrode for all-solid-state battery and electrode for all-solid-state battery
By using mixed dry coating and rolling process of particles and solid electrolyte powder in all-solid state battery electrodes, the problems of high porosity and insufficient loading are solved, and efficient and simplified electrode manufacturing is achieved.
Patent Information
- Application Number
- JP2024543946
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-01-26
- Filing Date
- 2023-01-27
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2043-01-27
AI Technical Summary
The prior art is difficult to effectively reduce the porosity of the all-solid-state battery electrode material layer, resulting in insufficient loading of electrode active material, and complex manufacturing process, making it difficult to achieve continuous production.
Particles containing electrode active material, conductive material and binder are mixed with solid electrolyte powder, and an electrode active material layer is formed on the current collector through dry coating and rolling processes to avoid the use of solvents and simplify the manufacturing process.
Significantly reduce the porosity of the electrode material layer, increase the loading of electrode active material, simplify the manufacturing process, and achieve efficient continuous production.
Smart Images

Figure 2025504530000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0012302 filed on January 27, 2022 and Korean Patent Application No. 10-2023-0010183 filed on January 26, 2023, and all contents disclosed in the documents of the relevant Korean patent applications are incorporated as part of this specification.
[0002] The present application relates to a method for producing an electrode for an all-solid-state battery and an electrode for an all-solid-state battery. [Background technology]
[0003] Currently, various batteries that can overcome the limitations of lithium secondary batteries are being researched from the viewpoints of battery capacity, safety, output, size, and miniaturization.
[0004] Representatively, research is being continuously conducted in academia and industry on metal-air batteries, which have a much larger theoretical capacity than lithium secondary batteries, all-solid-state batteries, which are safe and have no risk of explosion, supercapacitors, NaS batteries or RFBs (redox flow batteries), and thin film batteries, which are small in size.
[0005] Among them, all-solid-state batteries are batteries that replace the liquid electrolyte used in existing lithium secondary batteries with a solid, and since they do not use flammable solvents in the battery, they can greatly improve safety by preventing fires and explosions caused by the decomposition reaction of conventional electrolytes.In addition, they have the advantage of being able to dramatically improve the energy density relative to the mass and volume of the battery, since Li metal or Li alloy can be used as the anode material.
[0006] In particular, inorganic solid electrolytes in solid-state batteries can be divided into sulfide-based and oxide-based solid electrolytes. Among these, the solid electrolyte for which the most technological development has been made to date is the sulfide-based solid electrolyte, and even sulfide-based solid electrolyte materials with ionic conductivity close to that of organic electrolytes have been developed.
[0007] Meanwhile, unlike existing lithium secondary batteries that use liquid electrolytes, all-solid-state batteries use solid electrolytes, which means that the solid electrolyte cannot easily penetrate into the pores of the electrode active material layer, making it difficult to achieve physical contact between the electrode active material and the solid electrolyte. To solve this problem, a liquid solid electrolyte is generally used, but when using a liquid solid electrolyte, problems such as limitations on the selection of a solvent, poor dispersibility, and the generation of pores due to the drying of the solvent and the resulting reduction in the loading amount of the electrode active material may occur. In addition, a separate process is required to dry the solvent of the liquid solid electrolyte, and an isostatic pressing method such as cold isostatic pressing (CIP) or warm isostatic pressing (WIP) is used to reduce the porosity due to the drying of the solvent, which makes continuous processing impossible and complicates the process. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent Publication No. 10-2021-0045858 (April 27, 2021) Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a method for producing an electrode for an all-solid-state battery, which can reduce the porosity of an electrode active material layer, and an electrode for an all-solid-state battery produced thereby.
[0010] Another object of the present invention is to provide a method for manufacturing an electrode for an all-solid-state battery including an electrode active material layer having a high loading of an electrode active material by increasing the loading amount of the electrode active material, and an electrode for an all-solid-state battery manufactured thereby.
[0011] Another object of the present invention is to provide a method for producing an electrode for an all-solid-state battery, which can simplify the process, and an electrode for an all-solid-state battery produced thereby. [Means for solving the problem]
[0012] In one embodiment, the present invention provides a method for manufacturing an electrode for an all-solid-state battery, the method including the steps of: preparing granules including an electrode active material, a conductive material, and a binder; mixing the granules with a solid electrolyte powder; and disposing a mixture of the granules and the solid electrolyte powder on a current collector and applying pressure to form an electrode active material layer. The method also provides an electrode for an all-solid-state battery manufactured thereby. Effect of the Invention
[0013] One of the advantages of the present invention is that it provides a method for producing an electrode for an all-solid-state battery capable of reducing the porosity of an electrode active material layer, and an electrode for an all-solid-state battery produced thereby.
[0014] As another effect of the present invention, it is possible to provide a method for manufacturing an electrode for an all-solid-state battery including an electrode active material layer having a high loading of an electrode active material by increasing the loading amount of the electrode active material, and an electrode for an all-solid-state battery manufactured thereby.
[0015] Another advantage of the present invention is that it is possible to provide a method for producing an electrode for an all-solid-state battery that allows for simplified steps, and an electrode for an all-solid-state battery produced thereby. [Brief description of the drawings]
[0016] [Figure 1]1 shows an image of a mixture of granules and solid electrolyte powder produced according to an embodiment of the present invention observed under a scanning electron microscope (SEM), the image magnification is ×1,000. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an embodiment of the present invention will be described in detail. However, the following description should be understood as an example to help understand the present invention, and the following description should not be understood as limiting or restricting the present invention. In addition, the present invention is not limited to the attached drawings. A person skilled in the art can embody the present invention in various forms without departing from the technical idea of the present invention by referring to the following description and the attached drawings.
[0018] A method for manufacturing an electrode for an all-solid-state battery according to an embodiment of the present invention includes the steps of: preparing granules including an electrode active material, a conductive material, and a binder; mixing the granules with a solid electrolyte powder; and disposing the mixture of the granules and the solid electrolyte powder on a current collector and applying pressure to form an electrode active material layer.
[0019] According to one embodiment of the present invention, the granules are spherical particles containing an electrode active material, a conductive material, and a binder. Here, the term "spherical" does not mean a perfect sphere in the strict sense, but is used as a comprehensive concept including particles with a round shape. The fine particles of the electrode active material in a powder state can be bound together with the conductive material by a binder solution to grow into particles having a specific range of specifications.
[0020] According to one embodiment of the present invention, the granules are spherical particles having a diameter of 30 μm to 150 μm. Here, the spherical particles do not mean perfectly spherical particles, so the diameter means the largest value of the distance from any one point on the particle surface to another point on the surface. Specifically, the diameter of the granules may be 30 μm or more, 35 μm or more, 40 μm or more, 45 μm or more, 50 μm or more, 150 μm or less, 145 μm or less, 140 μm or less, 135 μm or less, 130 μm or less, 125 μm or less, 120 μm or less, 30 μm to 150 μm, 40 μm to 135 μm, 50 μm to 120 μm. If the diameter of the granules is less than the above range, the gap between the granules is small, and the amount of solid electrolyte powder that penetrates between the granules and coats them is reduced, which may make it difficult to achieve physical contact between the electrode active material and the solid electrolyte in an all-solid-state battery. If the diameter of the granules is more than the above range, the distance between the surface in contact with the solid electrolyte and the center of the granule may be large, and the electrode active material contained in the granule may not be fully utilized.
[0021] The method for manufacturing an electrode for an all-solid-state battery according to an embodiment of the present invention may be for manufacturing any one of a positive electrode and a negative electrode for an all-solid-state battery, more specifically, for manufacturing a positive electrode. In other words, the electrode for an all-solid-state battery according to an embodiment of the present invention may be any one of a negative electrode and a positive electrode, more specifically, the electrode for an all-solid-state battery may be a positive electrode.
[0022] When the electrode for an all-solid-state battery according to an embodiment of the present invention is a positive electrode, the electrode active material contained in the granules is not particularly limited as long as it can be used as a positive electrode active material for a lithium ion secondary battery. For example, a lithium transition metal oxide containing one or more transition metals can be used as the positive electrode active material. According to one embodiment of the present invention, the positive electrode active material is LiCoO2, LiNiO2, LiMnO2, Li2MnO3, LiMn2O4, Li(Ni a Co b Mn c )O2(0 <a<1、0<b<1、0<c<1、a+b+c=1)、LiNi 1‐y Co yO2 (O < y < 1), LiCo 1‐y Mn y O2, LiNi 1‐y Mn y O2 (O < y < 1), Li(Ni a Co b Mn c )O4 (0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2‐z Ni z O4 (0 < z < 2), LiMn 2‐z Co z O4 (0 < z < 2), LiNi 0.6 Co 0.2 Mn 0.2 It can be selected from the group consisting of O2 and this combination.
[0023] When the electrode for all-solid-state battery according to an embodiment of the present invention is a negative electrode, the electrode active material contained in the granules is not particularly limited as long as it is a material that can be used as the negative electrode active material of a lithium-ion secondary battery. For example, as the negative electrode active material, carbon such as non-graphitizable carbon and graphite-based carbon; Li x Fe2O3 (0 ≤ x ≤ 1), Li x WO2 (0 ≤ x ≤ 1), Sn x Me 1‐x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8) and other metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4 and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides, etc. One or more species selected from the above can be used. According to an embodiment of the present invention, the negative electrode active material can contain a carbon-based material and / or Si.
[0024] The conductive material contained in the granule according to an embodiment of the present invention is not particularly limited as long as it is a material that is located in the granule and can provide conductivity between the electrode active material and the electrolyte. For example, the conductive material may be one or a mixture of two or more conductive materials selected from the following: graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers such as VGCF (vapor grown carbon fiber); metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and polyphenylene derivatives.
[0025] The binder contained in the granule according to an embodiment of the present invention is mixed with the electrode active material and the conductive material, which are fine particles in a powder state, to bind the components and promote particle growth. Among solid electrolytes, sulfide-based solid electrolytes have moisture-sensitive properties, such as generating H2S gas when in contact with moisture, so it is preferable to remove moisture as much as possible from the time of forming the granules. According to an embodiment of the present invention, the binder is an organic binder. The organic binder refers to a binder that is dissolved or dispersed in an organic solvent, particularly N-methylpyrrolidone (NMP), and is distinguished from an aqueous binder that uses water as a solvent or dispersion medium. Specifically, the organic binder may be selected from the group consisting of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyimide, polyamide-imide, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butylene rubber, and fluororubber, but is not limited thereto.
[0026] The solid electrolyte powder according to an embodiment of the present invention may be selected from the group consisting of sulfide-based solid electrolyte powder, oxide-based solid electrolyte powder, and a combination thereof, and more specifically, may be a sulfide-based solid electrolyte powder. The sulfide-based solid electrolyte powder has advantages such as excellent ionic conductivity and stability, and is easily deformable, and is therefore preferably used.
[0027] According to an embodiment of the present invention, the solid electrolyte powder is a particle having an average particle diameter of 0.3 μm to 3 μm. Here, the average particle diameter does not mean the particle diameter of a perfectly spherical particle, but means the maximum value among the distances from any one point on the surface of the particle to another surface point. Specifically, the average particle diameter of the solid electrolyte powder may be 0.3 μm or more, 0.5 μm or more, 1.0 μm or more, 3 μm or less, 2.5 μm or less, 2 μm or less, 0.5 μm to 2.5 μm, 1 μm to 2 μm. If the average particle diameter of the solid electrolyte powder is less than the above range, the size of the solid electrolyte powder is smaller than the pore size of the granules, so that the amount of the solid electrolyte powder that penetrates between the granules and is coated is reduced, and physical contact between the electrode active material and the solid electrolyte in an all-solid-state battery is not easy. If the average particle diameter of the solid electrolyte powder exceeds the above range, the distance between the surface in contact with the solid electrolyte and the center of the granule is large, so that the electrode active material contained in the granules may not be fully utilized.
[0028] The sulfide-based solid electrolyte powder may include Li-P-S glass or Li-P-S glass ceramics that contain sulfur (S) and have the ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table. Non-limiting examples of such sulfide-based solid electrolyte powder include Li2S-P2S5, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2, and Li2S-GeS2-ZnS, and the sulfide-based solid electrolyte powder may include one or more of these.
[0029] Oxide-based solid electrolyte powders contain oxygen (O) and have the ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table. Non-limiting examples of oxide-based solid electrolyte powders include LLTO-based compounds, Li6La2CaTa2O 12 , Li6La2ANb2O 12 (A is Ca or Sr), Li2Nd3TeSbO12, Li3BO 2.5 N 0.5 , Li9SiAlO8, LAGP compounds, LATP compounds, Li 1+x Ti 2‐x Al x S y (PO4) 3‐y (where 0≦x≦1, 0≦y≦1), LiAl x Zr 2‐x (PO4)3 (where 0≦x≦1, 0≦y≦1), LiTi x Zr 2‐x (PO4)3 (where 0≦x≦1, 0≦y≦1), LISICON-based compounds, LIPON-based compounds, Perovskite-based compounds, NaSICON-based compounds, and LLZO-based compounds may be included.
[0030] Meanwhile, the solid electrolyte powder according to the embodiment of the present invention is distinguished from a liquid solid electrolyte in which a solid electrolyte powder is dissolved in a solvent. In other words, the solid electrolyte powder means a solid electrolyte powder in a solvent-free state.
[0031] In the step of preparing the granules, the granules may be prepared by a method generally used in the relevant technical field, and the method of preparation is not particularly limited. In preparing the granules, a binder solution may be added together with the fine particles of the electrode active material and the conductive material in a powder state to grow the size of the granule particles to a specific level. The solvent is dried from the formed granules, and the conductive material and the binder, which are relatively light in weight, are present on the surface of the granules. In addition, in the step of preparing the granules, the inside of the device may be rotated to make the granules spherical and separate each granule, and the centrifugal force acts on the granules due to the rotation, so that the conductive material and the binder are present on the surface of the granules. Specifically, the conductive material may be attached to at least a portion of the surface of the active material, and the binder may be present on the surface of the granules in a form coated on at least a portion of the surface of the active material. Meanwhile, the solvent that can be used in forming the granules is not particularly limited, and for example, N-methylpyrrolidone, isopropyl alcohol (IPA), dimethylformamide (DMF), dimethylacetamide (DMAc), benzene, toluene, tetrahydrofuran (THF), chloroform, etc. can be used.
[0032] In the step of mixing the granules with the solid electrolyte powder, the method of mixing the granules with the solid electrolyte powder is not particularly limited. For example, the granules can be mixed with the solid electrolyte powder using a mixer such as a thinky mixer. At this time, the granules are formed by drying the solvent, and the solid electrolyte powder is a solvent-free solid electrolyte powder, so the mixture of the granules and the solid electrolyte powder exists in a dry state, which is different from a slurry. In this case, the mixture can be mixed more uniformly than when the electrode active material and the solid electrolyte are mixed in a slurry state, so that the dispersibility can be improved. In particular, when the sulfide-based solid electrolyte is mixed with the electrode active material, the conductive material, and the binder in a slurry state, not only is it difficult to uniformly disperse each material, but there may also be a problem of migration of the conductive material and the binder to the surface of the electrode when manufacturing a high-loading electrode. According to the present invention, a granule is first prepared by removing a solid electrolyte that may cause a dispersibility problem, and then the solid electrolyte is mixed with the prepared granule, thereby making it possible to prepare an electrode that has excellent dispersibility among an electrode active material, a conductive material, a binder, and a solid electrolyte and can have a high loading of an electrode active material.
[0033] A mixture of granules and solid electrolyte powder according to one embodiment of the present invention is shown in Figure 1. Figure 1 shows the state before the granules and solid electrolyte powder are mixed and compressed, and in the mixture, the solid electrolyte powder covers the surfaces of the granules.
[0034] In the step of forming the electrode active material layer, the mixture of the granules and the solid electrolyte powder is disposed on the current collector by dry coating. In other words, no solvent is added to the mixture of the granules and the solid electrolyte powder, and the mixture is disposed on the current collector under dry conditions. Therefore, since a solvent drying process is not required, it is possible to prevent voids caused by the drying of the solvent and to simplify the process.
[0035] In addition, in the step of forming the electrode active material layer, pressing may be performed using a roll press. Specifically, the electrode active material layer may be formed by passing a mixture of granules and solid electrolyte powder disposed on a current collector together with the current collector between a pair of rollers and then heating and pressing the mixture. By dry-coating the mixture of granules and solid electrolyte powder on the current collector, a roll-to-roll continuous process is possible without applying an isostatic pressing method, which allows for simplification of the process.
[0036] When the electrode for an all-solid-state battery according to one embodiment of the present invention is a positive electrode, the current collector is a positive electrode current collector. Of course, the electrode manufactured in this manner can be a positive electrode. Also, when the electrode for an all-solid-state battery according to one embodiment of the present invention is a negative electrode, the current collector is a negative electrode current collector. Of course, the electrode manufactured in this manner can be a negative electrode.
[0037] The positive electrode current collector is not particularly limited as long as it has high conductivity without causing a chemical change in the all-solid-state battery, and may be, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may have fine irregularities on its surface to strengthen the bonding force with the positive electrode active material, and may be in various forms such as a film, sheet, foil, mesh, net, porous body, foam, nonwoven fabric, etc.
[0038] In addition, the negative electrode current collector is not particularly limited as long as it has conductivity without causing a chemical change in the all-solid-state battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. In addition, similar to the positive electrode current collector, the negative electrode current collector may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., having fine irregularities formed on the surface.
[0039] In the electrode for an all-solid-state battery manufactured by the manufacturing method for an electrode for an all-solid-state battery according to the embodiment described above, the porosity of the electrode active material layer may be less than 20%, and more preferably 15% or less. For example, the porosity of the electrode active material layer may be 19% or less, 18% or less, 17% or less, 16% or less, 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, or 10% or less, and more preferably 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, or 10% or less. In addition, the porosity of the electrode active material layer may be more than 0%, 0% or more, 1% or more, 2% or more, 3% or more, 4% or more, or 5% or more. Since the electrolyte of an all-solid-state battery is a solid phase, not a liquid phase, the lower the porosity, the greater the contact area between the electrode active material and the solid electrolyte, and the closer they are to each other, thereby exhibiting high ion conductivity. Therefore, in terms of ion conductivity, the lower the porosity of the all-solid-state battery electrode, the more preferable it is. According to the method for producing an electrode for an all-solid-state battery of the present invention, it is possible to produce an electrode for an all-solid-state battery including an electrode active material layer having a sufficiently low porosity so as to have excellent ion conductivity.
[0040] "Porosity" means the ratio of the volume of pores to the total volume of a structure, and is expressed in units of %, and can be used interchangeably with terms such as porosity, porosity, and porous ratio. Porosity can be measured by the BET (Brunauer-Emmett-Teller) measurement method using nitrogen gas or mercury penetration method (Hg porosimeter), but the method of measuring porosity is not limited thereto.
[0041] In addition, in the electrode for an all-solid-state battery manufactured by the manufacturing method for an electrode for an all-solid-state battery according to the embodiment described above, the loading amount of the electrode active material in the electrode active material layer may be 3 mAh / g or more. More specifically, the loading amount of the electrode active material in the electrode active material layer may be 3.0 mAh / g or more, 3.5 mAh / g or more, 4.0 mAh / g or more, 4.5 mAh / g or more, 4.6 mAh / g or more, 4.7 mAh / g or more, 4.8 mAh / g or more, 4.9 mAh / g or more, or 5.0 mAh / g or more. In addition, the loading amount of the electrode active material in the electrode active material layer may be 9.0 mAh / g or less, more specifically 9.0 mAh / g or less, 8.0 mAh / g or less, 7.0 mAh / g or less, 6.0 mAh / g or less, 5.5 mAh / g or less, or 5.0 mAh / g or less. According to the method for manufacturing an electrode for an all-solid-state battery of the present invention, granules including an electrode active material, a conductive material, and a binder are prepared, thereby preventing the problem of migration of the conductive material and the binder on the surface of the electrode, and the granules in which each material is uniformly dispersed are mixed with a soft all-solid-state electrolyte to reduce the porosity of the electrode active material layer, thereby providing an electrode for an all-solid-state battery in which the electrode active material is highly loaded, thereby improving the performance of the battery.
[0042] Meanwhile, the electrode for an all-solid-state battery according to an embodiment of the present invention may be manufactured by the above-described method for manufacturing an electrode for an all-solid-state battery according to an embodiment of the present invention, and thus includes a current collector and an electrode active material layer disposed on the current collector. Here, the electrode active material layer includes an electrode active material, a conductive material, a binder, and a solid electrolyte, and the solid electrolyte may be a sulfide-based solid electrolyte.
[0043] The description of each component included in the electrode for an all-solid-state battery according to an embodiment of the present invention may be applied in the same manner as described in the description of the manufacturing method of the electrode for an all-solid-state battery according to an embodiment of the present invention, so detailed description thereof will be omitted.
[0044] Preferred examples are presented below to aid in understanding the present invention. However, the following examples are provided merely to aid in understanding the present invention, and the present invention is not limited to the following examples.
[0045] [Example] LiNi as electrode active material 0.6 Co 0.2 Mn 0.2 O2 (NCM 622), carbon black as a conductive material, and polyvinylidene fluoride (PVDF) as a binder were mixed in a weight ratio of 94:3:3 (electrode active material: conductive material: binder) in N-methylpyrrolidone solvent to prepare a slurry, and the solvent was dried using a spray dry method to prepare granules with a diameter of approximately 60 μm (porosity: approximately 30%).
[0046] The prepared granules were mixed with Li2S-P2S5 sulfide-based solid electrolyte powder in a weight ratio of 80:20 (granules: solid electrolyte powder) in a thinky mixer, and the mixture of granules and solid electrolyte powder was placed on one side of an aluminum current collector with a thickness of about 100 μm.Then, the current collector and the mixture were pressed with a roll press at a temperature of 40°C and a gap of 80 μm to prepare a positive electrode for an all-solid-state battery with an electrode active material loading of 4.7 mAh / g and an electrode active material layer thickness of about 120 μm.
[0047] [Comparative Example] LiNi as electrode active material 0.6 Co 0.2 Mn 0.2O2 (NCM 622), carbon black as a conductive material, polyvinylidene fluoride (PVDF) as a binder, and Li2S-P2S5 as a solid electrolyte were mixed in anisole solvent at a weight ratio of 78:1:1:20 (electrode active material: conductive material: binder: solid electrolyte) using a Shinki mixer to prepare a slurry. The prepared slurry was then applied to one side of an aluminum current collector with a thickness of about 100 μm using a bar coater, and the solvent was evaporated using a vacuum dry method. After that, the current collector and the layered product including the slurry from which the solvent had been removed were sealed, and pressed with a cold isostatic press (CIP) at a pressure condition of 500 MPa to prepare a positive electrode for an all-solid-state battery with an electrode active material loading of 4.5 mAh / g and an electrode active material layer thickness of about 120 μm.
[0048] The porosity of the electrode active material layers according to the Examples and Comparative Examples of Preparation Examples is shown in Table 1.
[0049] [Table 1]
[0050] Referring to Table 1, the porosity of the electrode active material layer according to the embodiment is 10%, which is lower than the porosity of the electrode active material layer according to the comparative example, which is 20%. That is, it can be seen that the present invention can manufacture an electrode including a high-loading electrode active material layer having a low porosity.
[0051] Although an embodiment of the present invention and a specific example have been described above by way of example, this should be understood as a means to aid in the understanding of the present invention, and should not be understood as a means to limit the embodiment of the present invention. Those skilled in the art may appropriately modify and implement an embodiment of the present invention and an example by omitting, changing, or replacing all or part of the configuration of the embodiment of the present invention and an example, or adding other configurations, without departing from the technical idea of the present invention, by referring to this specification and the accompanying drawings. Therefore, the scope of protection of the present invention should be interpreted according to the following claims, and all technical ideas within the scope equivalent thereto should be interpreted as being included in the scope of the present invention.
[0052] All terms and expressions used in this specification should be understood as meanings that can be commonly understood by those having ordinary knowledge in the technical field to which this disclosure belongs unless otherwise defined. Furthermore, the terms and expressions used in this specification should be interpreted broadly and should not be interpreted in a restrictive sense.
[0053] In this specification, the word "comprising" does not exclude the presence or addition of one or more other elements other than those mentioned.
[0054] In addition, in this specification, the singular expression includes the plural form unless the context clearly indicates otherwise.
[0055] The embodiments described as examples in this specification can be combined with each other, and unless there is a contradiction, the content described in a particular embodiment can be applied to other embodiments in the same manner even if it is not described in the other embodiments.
Claims
1. preparing granules including an electrode active material, a conductive material, and a binder; mixing the granules with a solid electrolyte powder; and placing the mixture of the granules and the solid electrolyte powder on a current collector and pressing it to form an electrode active material layer. A method for manufacturing electrodes for all-solid-state batteries.
2. The porosity of the electrode active material layer is 15% or less. The method for producing the electrode for an all-solid-state battery according to claim 1 .
3. The loading amount of the electrode active material in the electrode active material layer is 3 mAh / g or more; The method for producing the electrode for an all-solid-state battery according to claim 1 .
4. In the step of forming the electrode active material layer, the mixture of the granules and the solid electrolyte powder is disposed on the current collector by solventless coating. The method for producing the electrode for an all-solid-state battery according to claim 1 .
5. In the step of forming the electrode active material layer, the pressing is performed using a roll press. The method for producing the electrode for an all-solid-state battery according to claim 1 .
6. In the step of preparing the granules, the conductive material is attached to at least a portion of the surface of the active material, and the binder is coated on at least a portion of the surface of the active material. The method for producing the electrode for an all-solid-state battery according to claim 1 .
7. The solid electrolyte powder is a sulfide-based solid electrolyte powder. The method for producing the electrode for an all-solid-state battery according to claim 1 .
8. The electrode active material layer is a positive electrode active material layer. The method for producing the electrode for an all-solid-state battery according to any one of claims 1 to 7.
9. A current collector; an electrode active material layer disposed on the current collector and including an electrode active material, a conductive material, a binder, and a sulfide-based solid electrolyte; The porosity of the electrode active material layer is less than 20%. Electrode for all-solid-state batteries.
10. The porosity of the electrode active material layer is 15% or less. The electrode for an all-solid-state battery according to claim 9 .
11. The loading amount of the electrode active material in the electrode active material layer is 3 mAh / g or more; The electrode for an all-solid-state battery according to claim 9 or 10.
Citation Information
Patent Citations
A manufacturing process of a cathode powder for a lithium-sulfur all-solid-state battery, and the lithium-sulfur all-solid-state baterry therefrom
KR1020160044951A
All-solid secondary battery electrode composite particles, method of manufacturing same, all-solid secondary battery electrode, and all-solid secondary battery
WO2019065030A1
KR10‐2021‐0045858